1988
DOI: 10.1007/bf00023528
|View full text |Cite
|
Sign up to set email alerts
|

Genetic strategies to determine the mode of 2n egg formation in diploid potatoes

Abstract: In this study, nineteen diploid potato clones (Solanum spp . 2n = 2x = 24) were identified as 2n egg producers on the basis of fruit set in 2x-4x crosses . The segregation of three genes mapped close to the centromere, Got-1 (1 .1 cM), Pgm-2 (2 .0 cM), and Sdh-1 (8 .3 cM), were analyzed in the tetraploid offspring in these 2x-4x crosses to discriminate between First Division Restitution (FDR) and Second Division Restitution (SDR) modes of 2n egg formation . The co-dominant nature of these markers lead to more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Analysis of the pattern of heterozygosity restitution within a linkage group is an alternative way to map the centromere compared with half-tetrad multilocus allelic configuration analysis Centromere mapping has been carried out in several crops (Douches and Quiros, 1988;Okagaki et al, 2008) and animals (Kauffman et al, 1995;Lindner et al, 2000), using HTA. In the present work, HTA has been carried out in two ways: by multilocus allelic conformation analysis, as described in Tavoletti et al (1996) and by comparison of observed and theoretical pattern of heterozygosity restitution rate within the linkage group under several models.…”
Section: Origin Of 2n Gamete-producing Triploids In Citrusmentioning
confidence: 99%
“…Analysis of the pattern of heterozygosity restitution within a linkage group is an alternative way to map the centromere compared with half-tetrad multilocus allelic configuration analysis Centromere mapping has been carried out in several crops (Douches and Quiros, 1988;Okagaki et al, 2008) and animals (Kauffman et al, 1995;Lindner et al, 2000), using HTA. In the present work, HTA has been carried out in two ways: by multilocus allelic conformation analysis, as described in Tavoletti et al (1996) and by comparison of observed and theoretical pattern of heterozygosity restitution rate within the linkage group under several models.…”
Section: Origin Of 2n Gamete-producing Triploids In Citrusmentioning
confidence: 99%
“…The procedure regarding tissue processing, electrophoresis, staining, and non1enclature is described by Douches and Quiros (1988); however, a TRIs-borate buffer, pH 8.3 and gel system (Stuber et al 1988) was substituted for the TRIs-citrate buffer, pH 7.8. The MDH, PGI, 6-PGDH and IDH enzyme systems were resolved in the histidine-citrate, pH 5.7 buffer system, while the PRX and PGM enzyme staining was reserved for the TRIs-borate, pH 8.3 system.…”
Section: Electrophoresismentioning
confidence: 99%
“…Provided there is no selection associated with this process, the haploids express the gametophytic output of the parental tetraploids. Our ability to esti mate double reduction in potato has been enhanced because: (1) the process of extracting haploids has become routine using the haploid pollinator technique (Hougas and Peloquin 1958) and has resulted in large numbers of haploids (Kotch and Peloquin 1987), and (2) researchers have developed codominant potato isozyme loci with the resolution to detect allelic dosage within a tetraploid locus (Staub et al 1984;Martinez Zapater and Olivier 1984;Quiros and McHale 1985;Douches and Quiros 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of appropriate meiotic mutants in potato, it has been possible to select genotypes that produce highly heterozygous FDR to relatively homozygous SDR populations of 2n-gametes (Ramanna, 1983;Werner & Peloquin, 1987;Werner et al, 1992;Douches & Quiros, 1988;Jongedijk et al, 1991;Bastiaanssen et al, 1996). It is believed that different meiotic aberrations can occur in one plant resulting in a mixture of FDR and SDR 2n-eggs (Conicella et al, 1991;Werner & Peloquin, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations (Douches & Quiros, 1987, 1988Jongedijk et al, 1991;Werner et al, 1992;Barone et al, 1995) lacked segregation data for several loci on a single chromosome, preventing a detailed examination of the degree of heterozygosity, the restitution mechanism and the number of crossovers per chromosome in each individual 2n-egg. This also prevented firm conclusions on the exclusive occurrence of one restitution mechanism or a mixture of several restitution mechanisms in a genotype.…”
Section: Introductionmentioning
confidence: 99%